Numerical analysis of Helmholtz resonators under linear and nonlinear excitation in subsonic flow - Camargo, Emerson Almeida (2021)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2021.